A forward-looking observatory - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Think of an observatory and you think of a place where people observe the heavens and other natural phenomena. Nowadays the word is used to describe an organisation which keeps an eye on developments in society. In the 1980s, observatories sprang up...